2013
DOI: 10.1182/blood-2012-09-457929
|View full text |Cite
|
Sign up to set email alerts
|

CD41 expression marks myeloid-biased adult hematopoietic stem cells and increases with age

Abstract: Key Points• Integrin CD41, thought to absent on adult HSCs, marks a novel subset of myeloidbiased long-term HSCs that becomes prevalent with age.• Loss of CD41 leads to transplantable hematopoietic defects that affect HSC survival and maintenance and are, in part, mediated by platelet loss.The hematopoietic stem cell (HSC) compartment is heterogeneous, yet our understanding of the identities of different HSC subtypes is limited. Here we show that platelet integrin CD41 (aIIb), currently thought to only transie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
268
4
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 293 publications
(302 citation statements)
references
References 50 publications
29
268
4
1
Order By: Relevance
“…CD41 has been reported to mark myeloid and megakaryocyte progenitors within the HSC compartment (Haas et al, 2015;Yamamoto et al, 2013), and it's expression increases with age (Gekas and Graf, 2013). Given that myeloid-restricted repopulating cells accumulate in aged mice (Dykstra et al, 2011;Sudo et al, 2000), we hypothesized that by examining CD41 expression we would better understand both the heterogeneity and the myeloid potential within aging HSC compartments.…”
Section: Increased Divisional History Marks Increased Myeloid Potentialmentioning
confidence: 96%
See 1 more Smart Citation
“…CD41 has been reported to mark myeloid and megakaryocyte progenitors within the HSC compartment (Haas et al, 2015;Yamamoto et al, 2013), and it's expression increases with age (Gekas and Graf, 2013). Given that myeloid-restricted repopulating cells accumulate in aged mice (Dykstra et al, 2011;Sudo et al, 2000), we hypothesized that by examining CD41 expression we would better understand both the heterogeneity and the myeloid potential within aging HSC compartments.…”
Section: Increased Divisional History Marks Increased Myeloid Potentialmentioning
confidence: 96%
“…CD41 + cells do not function as LT-HSCs at the clonal level in young adult mice (Yamamoto et al, 2013), but in the aging HSC compartment CD41 + HSCs have been shown to reside at the top of the hematopoietic hierarchy (Gekas and Graf, 2013). In order to understand how CD41 + cells develop LT-HSC potential with aging, we compared the H2BGFP label dilution of CD41 − and CD41 + cells within the GFP Hi LR-HSC fractions of young and aging mice.…”
Section: Cd41 + Slr-hscs Are Generated From Cd41 − Lr-hscs Throughoutmentioning
confidence: 99%
“…46 Previous studies have also reported that CD41 expression marks myeloid-biased adult hematopoietic stem cells and increases with age. 47 Unfortunately, none of these studies [42][43][44][45][46][47] evaluated megakaryocyte or erythroid output from these functionally defined HSC subsets. The identification of LMPPs suggested that a committed MegEprogenitor arises directly from an ST-HSC or early MPP without passing through a requisite CMP intermediate.…”
Section: Stem Cell Commitment To Megakaryocyte Differentiationmentioning
confidence: 99%
“…The gradual and progressive decline in stem cell function in humans is reflected in the results of several model systems in which GATA2 is required to maintain stem cell selfrenewal capacity Nottingham et al, 2007;de Pater et al, 2013). The absence of MLP/LMPP, loss of lymphoid and monocyte/DC haematopoiesis, with relative sparing of erythropoiesis and granulopoiesis, resembles an accelerated ageing phenotype (Gekas & Graf, 2013). It will be of interest to determine whether objective signs of this can be detected prematurely in GATA2 patients (Bakker & Passegue, 2013).…”
Section: Gata2 Mutation and Bone Marrow Failurementioning
confidence: 99%